Choose a Corner Strategy and 21st Century Skills in Argumentative Writing - Putu Dian Sawitri, N L (KnE Social Sciences, 2019)
This classroom action research is aimed at evaluating Choose a Corner strategy in fostering students’ higher order thinking skill in writing an Argumentative essay. As one of the sub-theme of the conference is the Four Cs (Communication, Collaboration, Critical Thinking, and Creativity) in the teaching of language, literature, and arts; the researcher tried to see how the strategy of Choosing a Corner would lead students in incorporating those four Cs particularly in creating a piece of Argumentative essay. The subject of the study were the fourth semester of English Education Study Program at the Faculty of teacher Training and Education Universitas Mahasaraswati Denpasar. The result of the study showed that Choose a Corner Strategy helped the students in thinking critically, analysing the situation more deeply, and providing logical reason and write it in an Argumentative Essay. The improvement is taking place because they have the chance to collaboratively exchange ideas and thoughts in the same corner. Even a struggling students could finished a convincing argumentative essay. This proves that choose a corner strategy not only just a collaborative strategy, but when we could formulate problem in such a way, it is one of the best strategy to promote critical thinking. Keywords: argumentative writing, 21